Discontinuation of Work Relationship In The Pandemic Time Covid-19 In Indonesian National Law - Eti Mul Erowati; Ikama Dewi (Media Komunikasi FPIPS, 2021)
The corona virus pandemic has shaken not only Wuhan, but also the world. This virus has spread widely to almost all countries in a short time. Meanwhile, in Indonesia the corona virus began to be detected when two Indonesian citizens (WNI) tested positive for the corona virus on March 1, 2020. The two Indonesians had previously had contact with a foreign national (WNA) from Japan who lived in Malaysia at an event. in Jakara. Based on data up to April 20, 2020, the number of victims due to the corona virus was 6,760 cases. A total of 590 of them died and 747 people were declared cured. Termination of Employment (PHK) is something that is very feared by employees. This is due to the chaotic economic conditions which have an impact on many companies that have to go out of business, and of course have an impact on the unilateral termination of employment by employers. To protect workers' rights due to layoffs, the Government as one of the elements in carrying out industrial relations has provided legal protection guarantees for workers whose employment has been terminated by employers as regulated in Chapter XII, precisely in Article 150-172 of Law Number 13 of 2003 concerning Manpower.